mHealth Series: mHealth project in Zhao County, rural China - Description of objectives, field site and methods - Michelle Helena van Velthoven; Ye Li; Wei Wang; Xiaozhen Du; Qiong Wu; Li Chen; Azeem Majeed; Igor Rudan; Yanfeng Zhang; Josip Car (Edinburgh University Global Health Society, 2013)
We set up a collaboration between researchers in China and the UK that aimed to explore the use of mHealth in China. This is the first paper in a series of papers on a large mHealth project part of this collaboration. This paper included the aims and objectives of the mHealth project, our field site, and the detailed methods of two studies.